Dispelling the shadow of fiscal dominance?: fiscal and monetary announcement effects for euro area sovereign spreads in the Corona pandemic - Havlik, Annika; Heinemann, Friedrich; Helbig, Samuel; Nover, Justus (ZEW-Kurzexpertise, 2021)
The COVID-19 pandemic has put the public finances of industrial countries under severe stress. The resulting recession has not only led to shortfalls in tax revenues but also to increased public expenditures. National governments have embarked on massive rescue packages to protect citizens and companies against the potentially disastrous health, social and economic consequences of pandemic disruptions. In addition, EU Member States have designed stimulus packages in order to support the economic recovery of affected sectors. For the euro area, the deep economic contraction and the soaring public debt levels have recalled bad memories from the years of the global financial crisis and the subsequent euro area debt crisis. The concern has been that this new and substantial solvency shock could once again trigger a vicious and self-enforcing cycle of rising sovereign bond spreads, a destabilization of the financial sector and a further decline in real economic activity. Subsequently, this could all lead to a new sovereign liquidity crisis similar to the contagion following the Greek government-debt crisis in spring 2010.
Keywords: Graue Literatur